Risk-based Stochastic Optimization of Evaporation Ponds as a Cost-Effective and Environmentally-Friendly Solution for the Disposal of Oil-Produced Water. (December 2020) - Izady, Azizallah; Nikoo, Mohammad Reza; Bakhtiari, Parnian Hashempour; Baawain, Mahad Said; Al-Mamari, Hilal; Msagati, Titus A.M.; Nkambule, Thabo T.I.; Al-Maktoumi, Ali; Chen, Mingjie; Prigent, Stephane
Graphical abstract: Highlights: Simultaneous effects of climatic and oil-produced water parameters are considered. Optimization framework determines the optimum dimensions of evaporation ponds. Stochastic evaporation scenarios are examined to include the uncertainties. Daily-based one-year experimental-data were collected from the oilfield. 20% increase in oil-produced water evaporation volume through the developed framework. Abstract: Evaporation ponds are a known cost-effective option which are also environmentally-friendly enough to be considered a viable solution for disposal of oil-produced water (OPW), especially in areas with high evaporation rates. However, there is no study to particularly relate OPW physico-chemical properties and climatic variables to optimum dimensions of evaporation ponds. This study therefore, presents a multi-objective-stochastic optimization framework, as a first attempt, to determine optimum dimensions of evaporation ponds considering simultaneous effects of climatic variables and OPW physico-chemical parameters on OPW evaporation (OPWE) rates. Daily-based experimental-data were collected from oilfield located at South-Eastern Arabian-Peninsula for a period of one-year. A model was derived using dimensional-analysis to estimate OPWE as a function of OPW physico-chemical properties, clear-water evaporation, and climatic variables. Fifty-stochastic evaporation scenarios were examined to include uncertainties associated with climatic and OPW parameters. Conditional-Value-at-Risk was utilized to reduce the risk of OPW overflow from evaporation ponds. A multi-objective NSGA-II model was developed to simultaneously maximize average volume of OPWE, minimize evaporation pond dimensions and also the risk of OPW overflow. Results show that the derived OPWE model performed exceptionally well in OPWE estimation by involving key parameters influencing the OPWE. Moreover, it was found that developed framework increased the magnitude of OPWE up to 20%. While inaccurate evaporation estimation can seriously increase probability of failure of evaporation ponds, the proposed framework was found to be efficient to determine the optimum dimensions of evaporation ponds for disposal of not only the OPW, but also other industrial and mining wastewater.